2016
DOI: 10.1103/physrevb.93.195415
|View full text |Cite
|
Sign up to set email alerts
|

Spin and charge transport induced by a twisted light beam on the surface of a topological insulator

Abstract: We theoretically study spin and charge transport induced by a twisted light beam irradiated on a disordered surface of a doped three dimensional topological insulator (TI). We find that various types of spin vortices are imprinted on the surface of the TI depending on the spin and orbital angular momentum of the incident light. The key mechanism for the appearance of the unconventional spin structure is the spin-momentum locking in the surface state of the TI. Besides, the diffusive transport of electrons unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Extensive theoretical (11)(12)(13) and some experimental studies have reported on the interaction between OAM of light and atomic media (14,15), generating new selection rules and optical responses. These studies suggest that the optical phase gradient modifies the excitation processes, but the results cannot be translated to obtain direct photocurrent generation for fabricating OAM-sensitive photodetectors.…”
mentioning
confidence: 99%
“…Extensive theoretical (11)(12)(13) and some experimental studies have reported on the interaction between OAM of light and atomic media (14,15), generating new selection rules and optical responses. These studies suggest that the optical phase gradient modifies the excitation processes, but the results cannot be translated to obtain direct photocurrent generation for fabricating OAM-sensitive photodetectors.…”
mentioning
confidence: 99%
“…For examples, the transfer to classical particles as an optical tweezer, [18,19] to exciton center-of-mass motion, [20] to the bounded electron in atoms, [21] or the laser ablation technique [22] have been demonstrated. Various theoretical predictions in condensed matter physics have also done: the optical absorption by semiconductors, [23] an electric current density in a semiconducting stripe, [24] the excitation of multipole plasmons in metal nanodisks, [25], the spin and charge transport on surface of topological insulators, [26], the generation of skyrmionic defects in chiral magnets, [27] and the creation of superconducting vortices, [28] among other things. However, it is known that an exchange of the optical OAM does not occur in an electric dipole transition in atoms and molecules.…”
Section: Introductionmentioning
confidence: 99%
“…13) From the point of classical mechanics, exerting a torque by transferring angular momentum from OV has been actively studied, for example, with particles rotating in an optical tweezers, [14][15][16] and the laser ablation technique. 17) In re- * 1517000122@campus.ouj.ac.jp cent years, coupling of twisted light with condensed matter also saw a considerable development, including such topics as generation of atomic vortex states by coherent transfer of OAM from photons to the Bose-Einstein condensate, 18) photocurrents excited by the OV beam-absorption in semiconductors and graphene, [19][20][21] excitation of multipole plasmons in metal nanodisks, 22) spin and charge transport on a surface of topological insulator, 23) generation of skyrmionic defects in chiral magnets. 24) However, whether OAM affects any spectroscopic selection rules via optically induced electronic transitions is still an open question.…”
Section: Introductionmentioning
confidence: 99%